(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This study has carefully explored arms proliferation and regional security problems, a reflection of insurgency in the Lake Chad region. The increase in arms proliferation across Nigeria and the entire Lake Chad is no doubt the function of the availability of light and small arms proliferation, playing an undeniable role in perpetuating violence from criminal related activities and destabilising peace, development and security. This study is anchored on the Frustration Aggression theory. The secondary data collection method was adopted for the work; and the study revealed that there is a high level of arms proliferation in Nigeria and the Lake Chad region. The porous state of border security in the Lake Chad region has led to arms proliferation in Nigeria and the States that make up this region. Arms proliferation takes place in Nigeria and the other Lake Chad States through multiple channels that include the States, illegal means, external support to insurgency groups in the region, from neighbouring countries to Lake Chad region, through cult groups, etc. Arms proliferation has so much affected development in Nigeria and the entire Lake Chad region. Finally, improving regional security in Nigeria and the entire Lake Chad region is a task that will require all stakeholders. Consequently, the study recommended containing the high level of arms proliferation in Nigeria and the Lake Chad region through all stakeholders; Nigeria playing an active role since it is the richest of all the States; control of the multiple channels of arms proliferation in Nigeria and the Lake Chad region; and efforts should be directed to boost development in the Lake Chad